2016
DOI: 10.1097/bot.0000000000000497
|View full text |Cite|
|
Sign up to set email alerts
|

Reaming Does Not Affect Functional Outcomes After Open and Closed Tibial Shaft Fractures

Abstract: Objectives We sought to determine the effect of reaming on 1-year SF-36 and SMFA scores from the Study to Prospectively Evaluate Reamed Intramedullary Nails in patients with Tibial Fractures (SPRINT). Design Prospective randomized controlled trial. 1,319 patients were randomized to reamed or unreamed nails. Fractures were categorized as open or closed. Setting 29 academic and community health centers across the US, Canada, and the Netherlands Patients/Participants 1,319 skeletally mature patients with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
0
23
2
2
Order By: Relevance
“…For the SMFA Bother, significant predictors of function were time from injury to follow-up assessment and open versus closed. 32 The main effect of reamed versus unreamed nailing was not a significant predictor in any of the functional subcategories. 32 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For the SMFA Bother, significant predictors of function were time from injury to follow-up assessment and open versus closed. 32 The main effect of reamed versus unreamed nailing was not a significant predictor in any of the functional subcategories. 32 …”
Section: Discussionmentioning
confidence: 83%
“…In a previous publication using data from the SPRINT trial, a mixed model repeated measures analysis was conducted by Lin et al 32 for the entire cohort to determine factors associated with HRQoL. They found that significant predictors of the SF-36 PCS were time from injury to follow-up assessment, open versus closed fracture, open versus closed by time from injury to follow-up assessment interaction, and treatment by time from injury to follow-up assessment interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial shaft fractures are common injuries and can be sustained via both high and low energy mechanisms in patients of all ages 1 . In skeletally mature patients with displaced tibial shaft fracture, the most common treatment is intramedullary nail fixation 2 , 3 , as operative treatment allows earlier definitive stabilization, avoids prolonged cast/brace treatment, and may allow for more rapid mobilization as well as faster time to union 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous negative consequences of lower extremity long bone fractures have been documented, including delayed healing, nonunion, malunion, and significantly delayed functional recovery [1, 2]. Specifically, at 1-year post-injury, most lower extremity long bone fracture patients have not regained their pre-injury function or quality of life [36]. Decreasing re-operations, improving fracture healing, and hastening functional recovery remain ongoing priorities for the orthopedic community.…”
Section: Introductionmentioning
confidence: 99%